Preparation and properties of trisodium pentacyano(isonicotinohydrazide)ferrate(II) hexahydrate and the kinetics of its substitution reactions - Blesa, Miguel Ángel; Funai, Irene A.; Morando, Pedro Juan; Olabe, José A.; Aymonino, Pedro J.; Ellenrieder, Guillermo (Royal Society of Chemistry, 1977)
Fil: Blesa, Miguel Ángel Comisión Nacional de Energía Atómica; Argentina